DEVELOPMENT OF SCIENCE TEACHING MATERIALS BASED GUIDED DISCOVERY FOR TRAINING SCIENCE PROCESS SKILLS - Imran, Yuliana Anggraini; Agustini, Rudiana; Taufikurohmah, Titik (JPPS (Jurnal Penelitian Pendidikan Sains), 2020)
The purpose of this research is to produce science teaching materials based guided discovery for training science process skills. This study adapted to 4D (four D models) that consists define, design, develop, and disseminate, but the stage is done only to develop stage. Teaching materials include syllabus, RPP, worksheets, student books, and science process skill test. This research tested at SMPN 5 Pamekasan. Feasibility of teaching material from the aspect of validity, practicality and effectiveness. Descriptive data were analyzed quantitatively. The validity results showed that teaching material is very valid. Practicality of teaching material show with the value of implementation learning process is excellent category and is supported by the activity of science process skills that have been shown in the study. The effectiveness of the teaching materials obtained from the increase pretest to posttest results of students science process skills with high category N Gain score and as much as 98% of students responded positively to learning guided discovery model. Based on the results, we can conclude that teaching materials based guided discovery that has been developed has been qualified validity, practicality, and effectiveness so that it can be used to train science process skills.